Cost-effectiveness Analysis of Еarly Medical Rehabilitation of Patients with Cerebral Stroke - Marina A. Shurupova; Alina D. Aizenshte; Galina E. Ivanova (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
Carrying out resuscitation procedures in the intensive care unit (ICU) aimed at maintaining and restoring the patient's vital functions, the use of specialized resuscitation equipment and bed rest simultaneously lead to aggravation of the patient's condition. The consequences of being in the ICU may also include the development of the post-intensive care syndrome (PIT syndrome), the prevention of which is the main goal of early rehabilitation with the participation of the multidisciplinary rehabilitation team of specialists (MDRT) led by a physical and rehabilitation medicine physician. Specialized medical rehabilitation carried out by MDRT is extremely beneficial for all neurological conditions, resulting in substantial savings in ongoing care costs, especially for ICU patients. The foreign and domestic research experience indicates a reduction in healthcare costs when introducing early rehabilitation in the ICU by reducing the duration of the patient's stay in the expensive round-the-clock bed and lowering the patient's home care costs or continuing rehabilitation activities at the second and third stages, as well as saving precious time for effective recovery of the developed functional deficits. It may seem that rehabilitation in the ICU with the participation of MDRT is more expensive than the work of one department doctor and a nurse. However, this article provides evidence of the economic efficiency of the MDRT work on the analysis of the results of the pilot project "Development of the Medical Rehabilitation System in the Russian Federation", as well as the analysis of clinical cases of the Federal Center of Brain Research and Neurotechnologies of the Federal Medical Biological Agency of Russia. So, in the absence of early rehabilitation in the ICU, the patient's stay is delayed and the number of re-hospitalizations to the unit increases. Thus, the results of early medical rehabilitation will have a direct impact on reducing the costs associated with bed-days reducing, providing patient's care, changing the working life of relatives, pensions of patients and their caregivers.